Edukasi Pemanfaatan Gedi Merah untuk Mengatasi Komplikasi Diabetes - Tandi, Joni; Handayani, Tien Wahyu; Aril, Moh; Polakitan, Grace Lovita (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Diabetes mellitus has become a serious health problem in Powelua Village with a prevalence of more than 15% of the adult population, accompanied by complications in vital organs and a high economic burden because the cost of treatment reaches IDR 1.5 million per month per patient. The community service program was implemented through comprehensive education on the use of red gedi to overcome diabetes complications, using lecture methods, interactive discussions, and practical demonstrations. Program evaluation was conducted through questionnaires distributed to 61 participants to measure the level of satisfaction and understanding. The evaluation results showed that the level of participant satisfaction reached an average of 84% (very good category), with three indicators reaching the very good category (80-100%) including the method of delivering material (100%), ease of understanding the material (100%), and the ability of the presenter to answer questions (80%). This program has succeeded in increasing community understanding of the use of red gedi as a safe and affordable alternative treatment for diabetes, although program adjustments are still needed to meet community expectations in future activities.